Get started with Microsoft Office 97 (Course Technology, 1997)
Getting started. Using Word 97. Microsoft Word projects. Microsoft Excel projects. Using Excel 97. Using Access 97. Microsoft Access projects. Using PowerPoint 97. Microsoft PowerPoint 97...